One wish - Harrison, Michelle, 1979- (Little, Brown and Company, 2016)
Twelve-year-old Tanya Fairchild spends her summer vacation in the seaside town of Spinney Wicket, where she makes a new friend, learns about the fairy realm, and discovers a magical wishing tree.